2018
DOI: 10.1016/j.trd.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the contribution of tunnels to the overall energy consumption of and carbon emissions from a railway

Abstract: Tunnels can contribute significantly to the overall energy consumption and carbon emissions of a railway, both in terms of embodied energy and emissions (those associated with the materials and the construction process) and in terms of operational energy and emissions (due to the increased air resistance experienced by a train inside a tunnel). Although tunnels may be a necessary component of railway infrastructure, it is important that their impact on carbon emissions is fully understood, especially when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Lee et al [ 12 ] quantified GHG emissions from construction modules covering earthworks, civil engineering activities (such as the construction of tunnels, viaducts, and bridges), railway tracks, passenger stations, and energy transmission and telecommunication systems for the entire HSR lines while identifying the key activity of each module and found about 92% of emissions originated from the use of materials. Pritchard and Preston [ 13 ] explored the contribution of tunnel engineering to the overall carbon emissions of railways based on multiple railway project cases and found that tunnels add significantly to both the embodied and operational energy consumption and GHG emissions of railway infrastructure. Kaewunruen et al [ 14 ] summarized material characteristics and calculated the carbon emissions and energy consumption of material production for tunnel and rail construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee et al [ 12 ] quantified GHG emissions from construction modules covering earthworks, civil engineering activities (such as the construction of tunnels, viaducts, and bridges), railway tracks, passenger stations, and energy transmission and telecommunication systems for the entire HSR lines while identifying the key activity of each module and found about 92% of emissions originated from the use of materials. Pritchard and Preston [ 13 ] explored the contribution of tunnel engineering to the overall carbon emissions of railways based on multiple railway project cases and found that tunnels add significantly to both the embodied and operational energy consumption and GHG emissions of railway infrastructure. Kaewunruen et al [ 14 ] summarized material characteristics and calculated the carbon emissions and energy consumption of material production for tunnel and rail construction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, due to incomplete statistical data (Sun et al, 2016), conventional studies on transportation carbon emissions have primarily focused on estimating the total emissions across the entire transportation sector to assist the government in formulating reasonable control policies (Zhang and Wei, 2015;Lopez et al, 2018). Relatively few studies have focused specifically on carbon emissions associated with specific modes of transportation; those that do exist have mostly employed quantitative measurements for air and railroad transportation (Chao, 2014;Edwards et al, 2016;Pritchard and Preston, 2018). Nevertheless, the transportation network is not a single system that relies on an individual mode of transportation; rather, it is an integrated system comprising various modes of transportation.…”
Section: Carbon Emissions From Transportationmentioning
confidence: 99%
“…There is evidence that studies on tailpipe emissions are more popular (Rocha et al 2018; De Martinis and Corman 2018; Meynerts et al 2017;Chester et al 2013) owing largely to the ease of their validation via comparison with other modes of rail transport (Esters and Marinov 2014). Contemporary studies by Pritchard and Preston (2018) concluded that studies which ignore the contribution of rail infrastructure might be misleading. They found that studies which discount the emissions of rail infrastructure by only considering use-phase emissions might erroneously promote railway transport as having lower carbon impacts on the environment.…”
Section: Literature Reviewmentioning
confidence: 99%